Caribbean policy response to the information age : a review of government information and communications technology policy and services in selected Caribbean countries (UN ECLAC Port of SpainTT, 2001)
Attempts to provide an overview of some of the major activities undertaken by some Caribbean governments and regional organizations in a real and serious attempt to seize the digital opportunity provided by the Internet and other technological applications which this technology has spawned.
Keywords: INFORMATION POLICY